Long-term exposure to air pollution and precocious puberty in South Korea - Oh, Jongmin; Choi, Jung Eun; Lee, Rosie; Mun, Eunji; Kim, Kyung Hee; Lee, Ji Hyen; Lee, Jungsil; Kim, Soontae; Kim, Hae Soon; Ha, Eunhee (Environmental Research, 2024)
Background and aim: The increasing prevalence of precocious puberty (PP) has emerged as a significant medical and social problem worldwide. However, research on the relationship between long-term air pollution exposure and PP has been relatively limited. We thus investigated the association between long-term air pollution exposure and the onset of PP in South Korea. Methods: We investigated a retrospective cohort using the Korea National Health Insurance Database. Six-year-old children born from 2007 to 2009 were examined (2013–2015). We included boys ≤10 years and girls aged ≤9 years who visited hospitals for early pubertal development, were diagnosed with PP per the ICD-10 (E228, E301, and E309), and received gonadotropin-releasing hormone agonist treatment. We analyzed data for boys up until 10 years old (60-month follow-up) and for girls up to 9 years old (48-month follow-up). We assessed the association between long-term air pollution exposure and the onset of PP using a Cox proportional hazard model. We estimated hazard ratios (HRs) and 95% confidence intervals (CIs) per 1 μg/m3 increase in fine particulate matter (PM2.5) and particulate matter (PM10) and per 1 ppb increase in sulfur dioxide (SO2), nitrogen dioxide (NO2), and ozone (O3). Results: This study included 1,205,784 children aged six years old between 2013 and 2015. A positive association was found between the 48-month moving average PM2.5 (HR: 1.019; 95% CI: 1.012, 1.027), PM10 (HR: 1.009; 95% CI: 1.006, 1.013), SO2 (HR: 1.037; 95% CI: 1.018, 1.055), and O3 (HR: 1.006; 95% CI: 1.001, 1.010) exposure and PP in girls but not boys. Conclusions: This study provides valuable insights into the harmful effects of air pollution during childhood and adolescence, emphasizing that air pollution is a risk factor that should be managed and reduced.
Keywords: Air pollution exposures; Child; Confidence interval; Follow up; Hazard ratio; Particulate Matter; PM 10; PM 2.5; Precocious puberties; South Korea; Air Pollutants; Air Pollution; Child; Child, Preschool; Environmental Exposure; Female; Humans; Male; Ozone; Particulate Matter; Puberty, Precocious; Republic of Korea; Retrospective Studies; Air pollution; Children; Particulate matter; Precocious puberty; South Korea